2020
DOI: 10.1007/s00268-020-05678-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Preoperative Examinations for Non‐occlusive Mesenteric Ischemia: A Multicenter Retrospective Project Study Conducted by the Japanese Society for Abdominal Emergency Medicine

Abstract: Background Non-occlusive mesenteric ischemia (NOMI) has a high mortality rate, but the analyses of preoperative prognostic factors for improving survival in patients suspected of having NOMI are scarce. We aimed to analyze the prognostic factors of preoperative examinations for NOMI. Methods The clinical data of 224 patients with NOMI were retrospectively collected for a multicenter survey. Clinicophysiological factors were compared between the survivors and non-survivors (N = 107/117) and between the operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
(42 reference statements)
0
26
1
Order By: Relevance
“…While emergency laparotomy for suspected MOMI has been recommended, the clinical outcomes have not improved as we expected [6][7][8][9]. Indeed, it is di cult to determine an appropriate bowel resection line by intraoperative ndings due to the potentially multifocal and progressive nature of the ischemic disease.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While emergency laparotomy for suspected MOMI has been recommended, the clinical outcomes have not improved as we expected [6][7][8][9]. Indeed, it is di cult to determine an appropriate bowel resection line by intraoperative ndings due to the potentially multifocal and progressive nature of the ischemic disease.…”
Section: Introductionmentioning
confidence: 98%
“…There have been several studies to evaluate risk factors for the development of NOMI and factors in uencing the surgical outcomes [6][7][8][9]. However, the criteria for the decision of non-operative management remain poorly de ned.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there is a spectrum of severity, from mild mucosal ischemia to transmural bowel necrosis and perforation, in the manifestation of NOMI [ 3 ]. Some previous studies showed successful outcomes of conservative treatment for the initial stages, with limited bowel wall ischemia [ 8 , 12 ]. Nonetheless, the decision-making of conservative treatment for NOMI is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Acute mesenteric ischemia (AMI) is a life-threatening condition associated with high mortality, ranging from 20 to 77% [1][2][3][4][5][6][7] . However, the different mechanisms leading to AMI do not share the same prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the two diseases are very different from a pathophysiological point of view, most of the previously published studies examining the prognosis of AMI have included both OMI and NOMI [1][2][3] . Furthermore, among the studies focused on NOMI 4,6 , a substantial proportion of patients did not undergo laparotomy, resulting in a potential bias in predicting prognosis, since the de nition of NOMI is neither standardized nor consensual.…”
Section: Introductionmentioning
confidence: 99%